Heat capacity and thermodynamic functions of thulium tellurites in the range of 298.15–673 K - Rustembekov, K. T.; Dyusekeeva, A. T.; Bekturganova, A. Zh.; Kasenov, B. K.; Makhatova, N. A.; Fomin, V. N. (Pleiades Publishing, 2016)
The isobaric heat capacity of double thulium tellurites is studied via dynamic calorimetry in the range of 298.15–673 K. It is used as the basis for deriving the equation C p o ∼ f(T) and determining the thermodynamic functions. Dependences C p o ∼ f(T) are found to have second-order phase λ-transitions.
Keywords: sodium‒thulium tellurites; potassium‒thulium tellurites; heat capacity; thermodynamic functions